Influence of gas atmosphere on electron-induced reactions of polyacrylonitrile homopolymer powder at elevated temperature. (May 2019) - Gohs, Uwe; Böhm, Robert; Brünig, Harald; Fischer, Dieter; Leopold, Anne-Katrin; Malanin, Mikhail; Müller, Michael-Thomas; Cherif, Chokri; Richter, Mirko; Wolz, Daniel Sebastian Jens; Jäger, Hubert
Abstract: The thermal stabilization of polyacrylonitrile precursor fibers is a highly exothermic and time-consuming process. In several investigations, the reduction of thermal stabilization time was demonstrated for an irradiation of polyacrylonitrile at room temperature in different atmospheres. Since electron induced chemical reactions strongly depend on the polymer chain segment mobility, the present investigation reports the electron treatment of polyacrylonitrile homopolymer (PAN) powder in air and nitrogen atmosphere at an average temperature of 125 °C. The irradiation temperature was precisely selected in order to study the electron induced reactions and changes of PAN structure at temperatures above the glass transition temperature, but below the initiation temperature of thermal induced reactions. Based on several analyses performed mainly at room temperature, the significant influence of gas atmosphere during the EB treatment of PAN powder at an average temperature of 125 °C on the number of trapped radicals, the ratio of chain scission density to density of crosslinked units, the level of fluorescence, the EB induced changes of constitution of PAN, the extent of cyclization and the residual mass at 800 °C under the conditions of TGA was shown. Highlights: Cyclization of PAN can be induced by an EB treatment at 125 °C. Maximum extent of cyclization was achieved by EB treatment in air. Strong PAN network led to reduced values of residual mass at 800 °C. Cyclization and residual mass are controlled by chain scission to crosslinking ratio. Graphical abstract: fx1